2014
DOI: 10.19173/irrodl.v15i4.1790
|View full text |Cite
|
Sign up to set email alerts
|

Learners’ views regarding the use of social networking sites in distance learning

Abstract: In this study, it was aimed to examine the use of learning management systems supported by social networking sites in distance education and to determine the views of learners regarding these platforms. The study group of this study, which uses a qualitative research approach, consists of 15 undergraduate students who resumed their education in Turkey. The data were gathered via a semi-structured interview form which consists of open-ended questions. Content analysis was used in the analysis of the data.Accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Based on the self-reported data, it shows a negative relationship between the frequency of engaging in Facebook chat and time spent preparing for class as well. This finding seems to be consistent with the study reported by Ozmen and Atici [17] that overuse of chat can become a distraction for learning since chat takes away the time that initially should have been allocated for study.…”
Section: Student Perspectivessupporting
confidence: 92%
See 2 more Smart Citations
“…Based on the self-reported data, it shows a negative relationship between the frequency of engaging in Facebook chat and time spent preparing for class as well. This finding seems to be consistent with the study reported by Ozmen and Atici [17] that overuse of chat can become a distraction for learning since chat takes away the time that initially should have been allocated for study.…”
Section: Student Perspectivessupporting
confidence: 92%
“…In order to study the impact of social media in higher education setting, many researchers conducted explorative studies to investigate the students' perceived learning experience [4,7,12,17,[21][22][23]. Veletsianos and Navarrete [24] conducted a case study utilizing Elgg as the online social network in an online course, and investigated students' perceived learning experience.…”
Section: Student Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such widespread use of social networks has brought to mind the importance of the use of these environments in educational platforms. Social sharing networks may provide contributions to the education environment such as improving communication, providing an opportunity to meet such environments, and eliminating communication problems related to the contributions of activities carried out on the social networking site (Özmen and Atici, 2014). However, it is seen that such social networks are perceived and used more for social purposes rather than educational purposes (Roblyer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These include lack of privacy, deceptions, and false information. Özmen and Atıcı [21] have recently examined the use of learning management systems supported by SNSs in distance education in Turkey. The researchers investigated the views of fifteen participants regarding these platforms.…”
Section: Current Uses Of Social Networking Sites Amongmentioning
confidence: 99%